2012
DOI: 10.1111/jvh.12043
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis viruses (other than hepatitis B and C viruses) as causes of hepatocellular carcinoma: an update

Abstract: Chronic hepatitis B and C virus infections are universally accepted as causes of hepatocellular carcinoma in humans. Hepatitis A and E viruses cause only acute self-limiting infections of the liver. Of the remaining hepatitis viruses - Delta hepatitis, hepatitis G (GB-C), TT and SEN - all have at some time been incriminated as causes of hepatocellular carcinoma. Delta hepatitis virus requires helper functions from hepatitis B virus to become invasive. Chronic Delta/hepatitis B viral co-infection runs a more se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 105 publications
(177 reference statements)
0
21
0
3
Order By: Relevance
“…Chronic HDV infection frequently is associated with active chronic hepatitis that leads to cirrhosis in 70% patients in 5 to 10 years. 8,9 Patients with chronic HDV infections have more rapidly progressive liver damage than patients infected with HBV alone. 10 The incidence of cirrhosis is 3-fold higher in patients with HBV/HDV chronic coinfection than chronic HBV monoinfection, with a higher risk of early decompensation and development of hepatocellular carcinoma (HCC).…”
Section: Hepatitis B-and Hepatitis D-virus-relatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic HDV infection frequently is associated with active chronic hepatitis that leads to cirrhosis in 70% patients in 5 to 10 years. 8,9 Patients with chronic HDV infections have more rapidly progressive liver damage than patients infected with HBV alone. 10 The incidence of cirrhosis is 3-fold higher in patients with HBV/HDV chronic coinfection than chronic HBV monoinfection, with a higher risk of early decompensation and development of hepatocellular carcinoma (HCC).…”
Section: Hepatitis B-and Hepatitis D-virus-relatedmentioning
confidence: 99%
“…10 The incidence of cirrhosis is 3-fold higher in patients with HBV/HDV chronic coinfection than chronic HBV monoinfection, with a higher risk of early decompensation and development of hepatocellular carcinoma (HCC). 9,11 Therefore, HDV infection in the world is an important health burden. The only established treatment for chronic HDV is interferon at high doses, but interferon therapy is associated with therapeutic success in only 25% to 30% treatments.…”
Section: Hepatitis B-and Hepatitis D-virus-relatedmentioning
confidence: 99%
“…In concordance, Tangkijvanich et al (2003) also reported no differences between SENVinfected and non-infected patients regarding severity of chronic liver disease and HCC. Recently, no evidence has been produced to indicate that SEN virus causes HCC (Kew, 2013). On the contrary, another study documented that SENV co-infection may influence the histopathological features of the livers of patients with CHC but does not affect the outcome of patients with type C chronic liver disease.…”
mentioning
confidence: 99%
“…It has also been detected in various types of carcinoma including leukemia and colorectal cancer. However, the pathogenicity of TTV at present is unclear [7,18,20,26,27]. Due to the lack of available tissue-culture methods, TTV infection is often diagnosed on the basis of TTV-DNA detection by PCR.…”
Section: Introductionmentioning
confidence: 99%
“…This needs further extensive investigation. TTV shows a high prevalence both in healthy and in diseased individuals globally [19][20][21]. The virus has been detected in nearly all tissues of the body [22].…”
Section: Introductionmentioning
confidence: 99%